Rethinking the dispersal of Homo sapiens out of Africa. Issue 4 (8th July 2015) - Groucutt, Huw S.; Petraglia, Michael D.; Bailey, Geoff; Scerri, Eleanor M. L.; Parton, Ash; Clark‐Balzan, Laine; Jennings, Richard P.; Lewis, Laura; Blinkhorn, James; Drake, Nick A.; Breeze, Paul S.; Inglis, Robyn H.; et al.
<x xml:space="preserve">Abstract</x> Current fossil, genetic, and archeological data indicate that Homo sapiens originated in Africa in the late Middle Pleistocene. By the end of the Late Pleistocene, our species was distributed across every continent except Antarctica, setting the foundations for the subsequent demographic and cultural changes of the Holocene. The intervening processes remain intensely debated and a key theme in hominin evolutionary studies. We review archeological, fossil, environmental, and genetic data to evaluate the current state of knowledge on the dispersal of Homo sapiens out of Africa. The emerging picture of the dispersal process suggests dynamic behavioral variability, complex interactions between populations, and an intricate genetic and cultural legacy. This evolutionary and historical complexity challenges simple narratives and suggests that hybrid models and the testing of explicit hypotheses are required to understand the expansion of Homo sapiens into Eurasia.